Sengketa Kepemilikan Sertifikat Ganda Hak Milik Atas Tanah: Analisis Yuridis Terhadap Putusan PTUN Kupang Nomor : 13/G/2018/PTUN-KPG - Tanaos, Jonsilas; Eneng Nita Juwita (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Land is an object of wealth that is always closely related to all human activities and is also inseparable from all national development activities. Because of its strategic position and limited nature, it gives rise to special treatment for land protected by law. This article is reviewed with the title: Dispute on the Ownership of Multiple Land Ownership Certificates (Judicial Analysis of Kupang PTUN Decision Number: 13/G/2018/PTUN-Kpg) which aims to answer questions about the Process for Resolving Disputes on Ownership of Multiple Land Ownership Certificates. This research is juridical research carried out using a library approach, case study approach, conceptual approach and formal juridical approach or statute approach. The process of completing the double certificate of ownership of land rights initially started from an approach taken by National Land Agency officials together with the parties. The next step is resolution through the Judicial Body by means of parties who feel their legal interests have been harmed by the State Administrative Decree, filing a lawsuit with a judge at the State Administrative Court. The Kupang State Administrative Court judge who examined and tried, then decided based on the facts of the trial and granted the plaintiff's claim and sentenced the Defendant to abort two land ownership certificates and sentenced the Defendant and Defendant II to Intervene to pay the court costs.